2021
DOI: 10.3390/jpm11111061
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton Microscopy for Identifying Collagen Signatures Associated with Biochemical Recurrence in Prostate Cancer Patients

Abstract: Prostate cancer is a heterogeneous disease that remains dormant for long periods or acts aggressively with poor clinical outcomes. Identifying aggressive prostate tumor behavior using current glandular-focused histopathological criteria is challenging. Recent evidence has implicated the stroma in modulating prostate tumor behavior and in predicting post-surgical outcomes. However, the emergence of stromal signatures has been limited, due in part to the lack of adoption of imaging modalities for stromal-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…MPM not only has the advantage of resolution comparable to digital histopathology, but also has the advantages of label-free, low photobleaching and photodamage, and a high imaging contrast. Therefore, MPM has been receiving a lot of attention in the field of basic and applied research in medical pathology diagnosis, especially in the clinical translation of tumor pathological diagnosis [40][41][42][43]. In this study, our results demonstrate that MPM can be used to detect the different morphologies of IMPC cell clusters, and to identify stromal pathological changes in tumor microenvironment such as collagen changes, TILs, lymphatic vascular invasion.…”
Section: Quantitative Analysismentioning
confidence: 68%
“…MPM not only has the advantage of resolution comparable to digital histopathology, but also has the advantages of label-free, low photobleaching and photodamage, and a high imaging contrast. Therefore, MPM has been receiving a lot of attention in the field of basic and applied research in medical pathology diagnosis, especially in the clinical translation of tumor pathological diagnosis [40][41][42][43]. In this study, our results demonstrate that MPM can be used to detect the different morphologies of IMPC cell clusters, and to identify stromal pathological changes in tumor microenvironment such as collagen changes, TILs, lymphatic vascular invasion.…”
Section: Quantitative Analysismentioning
confidence: 68%
“…The first reports showed that there is an increase on the collagen alignment with the increase of the Gleason grade [33, 34]. In addition, recent results [36] for 64 patients showed that the collagen morphology characteristics are associated with biochemical recurrence.…”
Section: Introductionmentioning
confidence: 99%